Basal cell adenoma mimicking adenoid cystic carcinoma on FNAC- A Case Report - Singh, Arjun; Sharma, Rashi; Nema, S K (International Journal of Medical Research and Review, 2014)
A 40-year-old-female presented with a right parotid swelling. It was diagnosed as adenoid cystic carcinoma on FNAC. On histopathology final diagnosis of basal cell adenoma was made. Basal cell adenoma is a rare and benign basaloid neoplasm of the salivary gland. The other basaloid neoplasms are pleomorphic adenoma, basal cell adenocarcinoma, adenoid cystic carcinoma, metastatic basal cell carcinoma, metastatic squamous cell carcinoma and small cell carcinoma. Differentiating basaloid neoplasms on FNAC pose diagnostic difficulties. The goal is to discuss problems and pitfalls in FNAC diagnosis of basal cell adenoma and to emphasize on cautious approach while diagnosing basaloid neoplasm on cytology.